DISPUTED KNOWLEDGES AND TERRITORIES OF RESISTANCE: INSURGENT EPISTEMOLOGIES, COLONIALITY OF KNOWLEDGE AND CHALLENGES FOR THINKING POSSIBLE FUTURES - Antonio Nunes Aguiar, Jose (Revista Gênero e Interdisciplinaridade, 2025)
This article proposes a critical analysis of contemporary epistemological disputes by articulating knowledge, power, and territory, focusing on the emergence of insurgent epistemologies within territories of resistance. It argues that the dominant epistemology, inherited from the European Enlightenment and historically captured by capitalism, has functioned as an instrument of cultural hierarchization, cognitive exclusion, and destruction of the knowledge produced by Indigenous peoples, Black populations, and socially marginalized groups. The article discusses how the coloniality of knowledge operated systematic processes of epistemicide while highlighting historical practices of resistance and, in the contemporary context, movements of epistemological recovery. Drawing on decolonial studies, African philosophy—especially the thought of Severino Elias Ngoenha—and critical social theory, the text argues that territories of resistance are legitimate spaces of epistemological production and imagination of possible futures. It concludes that dismantling hegemonic epistemology and recognizing epistemological plurality are essential conditions for building a science committed to cognitive justice and social transformation.